Selectfluor-mediated transformation of cedrol and cedrene under the Ritter reaction conditions - Olga A. Zhupikova; Vyacheslav I. Krasnov; Olga I. Yarovaya; Andrey A. Nefedov; Vadim V. Bardin; Yuri V. Gatilov; Artem D. Rogachev; Nariman F. Salakhutdinov; Mikhail V. Khvostov (Journal of Fluorine Chemistry, 2025)

Correction to: A pair of gametologous genes provides further insights into avian comparative cytogenomics - Alexei A. Sazanov; Anna L. Sazanova; Mikhail D. Nefedov; Darren K. Griffin; Michael N. Romanov (Biologia, 2023)

A pair of gametologous genes provides further insights into avian comparative cytogenomics - Alexei A. Sazanov; Anna L. Sazanova; Mikhail D. Nefedov; Darren K. Griffin; Michael N. Romanov (Biologia, 2023)
Exploration of avian gametologous genes, i.e., homologous genes located on both the Z and W chromosomes, provides a crucial information about the underlying mechanism pertaining to the evolution of these chromosomes. The domestic chicken ( Gallus gallus (Linnaeus 1758); GGA) traditionally serves as the primary reference subject of these comparative cytogenomic studies. Using bioinformatic, molecular (overgo BAC library scanning), and cytogenetic (BAC-based FISH) techniques, we have investigated in detail a pair of UBE2R2 / UBE2R2L gametologs. By screening a gridded genomic jungle fowl BAC library, CHORI-261, with a short labeled UBE2R2L gene fragment called overgo probe, we detected seven specific clones. For three of them, CH261-019I23, CH261-105E16, and CH261-114G22, we identified their precise cytogenetic location on the Gallus gallus W chromosome (GGAW). They also co-localized with the UBAP2L2 gene on the, as was shown previously, along with the CH261-053P09 BAC clone also containing the GGAW-specific UBE2R2L DNA sequence. The fine mapping of the UBE2R2 / UBE2R2L homologs in the chicken genome also shed the light on comparative cytogenetic aspects in birds. Our findings provided further evidence that bird genomes moderately changed only during evolution and are suitable for successful use of interspecies hybridization using both overgo-based BAC library screen and BAC-based FISH.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)